Advocacy, activism, and lobbying: How variations in interpretation affects ability for academia to engage with public policy - Nasreen S. Jessani; Brenton Ling; Carly Babcock; Akshara Valmeekanathan; David R. Holtgrave (Public Library of Science (PLoS), 2022)
Research and teaching are considered core-responsibilities for academic researchers. "Practice" activities however are viewed as ancillary, despite university emphasis on their importance. As funders, governments, and academia address the role of research in social impact, the deliberations on researcher activism, advocacy and lobbying have seen a resurgence. This study explores the perceptions of 52 faculty and 24 government decisionmakers on the roles, responsibilities, and restrictions of an academic to proactively engage in efforts that can be interpreted under these three terms. Data was coded through inductive thematic analysis using Atlas.Ti and a framework approach. We found that discordant perceptions about how much activism, advocacy and lobbying faculty should be engaging in, results from how each term is defined, interpreted, supported and reported by the individuals, the School of Public Health (SPH), and government agencies. Influential faculty factors included: seniority, previous experiences, position within the institution, and being embedded in a research center with an advocacy focus. Faculty views on support for advocacy were often divergent. We surmise therefore, that for effective and mutually beneficial collaboration to occur, academic institutions need to align rhetoric with reality with respect to encouraging modes and support for government engagement. Similarly, government agencies need to provide more flexible modes of engagement. This will contribute to alleviating confusion as well as tension leading to more effective engagement and consequently opportunity for evidence-informed decision making in public health globally.